Separation and characterisation of mineral oil slicks and newly formed sea ice in L-band synthetic aperture radar - Johansson, Malin; Espeseth, Martine; Brekke, Camilla; Skrunes, Stine (IGARSS 2019 - 2019 IEEE International Geoscience and Remote Sensing Symposium, 2019)
Maritime activities in the Arctic Ocean is increasing and consequently the risk for an oil spill there is rising. Synthetic Aperture Radar (SAR) is used operationally to detect and monitor oil slicks and for sea ice monitoring and observations. Leads are often used for ship routing and within the leads newly formed sea ice is often present. Separation between the low backscatter areas that constitutes oil slicks and newly formed sea ice is therefore important. Here we compare fully polarimetric L-band SAR images overlapping both oil slicks and newly formed sea ice. For the oil slicks airborne Uninhabited Aerial Vehicle SAR (UAVSAR) images are used and for the newly formed sea ice an ALOS-2 PALSAR-2 image is used. Using a set of multi-polarization features we observe that the coefficient of variation of the polarization difference can be used to separate the two.